Food neophobia among university students in Saudi Arabia: a cross-sectional survey of prevalence and predictor analysis - Alshahrani, Najim Z. (Frontiers in Public Health, 2025)
IntroductionDue to the absence of scientific information on food neophobia (i.e., fear or reluctance to try new or unfamiliar foods) among young adults in Saudi Arabia, the aim of this study was to assess the prevalence and predictors of food neophobia in Saudi university students.MethodsThis cross-sectional study included 480 students from two public universities of Saudi Arabia. The data was collected via an internet-based structured questionnaire. Participants’ sociodemographic, health and behavioral information were included as explanatory variables (15 variables). Participants’ food neophobia was assessed using a10-item validated food neophobia scale. A logistic regression model was fitted to find out the predictors of food neophobia.ResultsApproximately half of the participants (49.6%) exhibited food neophobia. Participants who engaged in regular physical exercise had a lower risk of developing food neophobia than their counterparts (AOR: 0.43, 95%CI: 0.20–0.92). Participants with food allergies (AOR: 4.36, 95%CI: 2.73–6.94) and disordered eating attitudes (AOR: 2.52, 95%CI: 1.27–5.02) and who took dietary supplements (AOR: 6.76, 95%CI: 3.54–12.90) were more likely to be food neophobic. Moreover, participants’ preferences for fish and sea food (rs = −0.150), milk and dairy products (rs = −0.309,), chocolate and candies (rs = −0.329) and snacks, chips, and nuts (rs = −0.166) were significantly correlated with food neophobia.ConclusionA higher level of food neophobia was observed among surveyed university students in Saudi Arabia. Several factors, such as regular physical exercise, food allergies, dietary supplement consumption, and disordered eating attitudes, were found to be associated with food neophobia. To provide empirical evidence on food neophobia, additional research with large and representative samples could be performed in other regions of Saudi Arabia.